Membranes Containing Nanoparticles Incorporated with Metronidazole for Improved Permeability to Promote Periodontal Tissue Recovery - Chen, Yongshi; Wu, Hao; Lu, Geng; Zhu, Yi; Ban, Junfeng; Li, Xiaofang (Current Nanoscience, 2025)
BackgroundInfection is the main reason for the failure of the clinical application of guided tissue regeneration (GTR).ObjectiveThe aim of this study is to develop a membrane containing nanoparticles incorporated with the antimicrobial drug metronidazole (MTZ-NPs Membrane) to enhance drug permeation delivery into cells and promote periodontal tissue recovery and regeneration.MethodsWe prepared membranes containing nanoparticles incorporated with metronidazole (MTZ-NPs Membrane) and characterized the properties, such as mechanical properties, physicochemical properties, and release. Coumarin-6 was used to prepare a membrane containing nanoparticles incorporated with Coumarin-6 (C6-NPs Membrane) to evaluate the efficiency of the nanoparticles-loaded membranes on transmembrane entry into cells. Moreover, in vivo experiments were conducted to assess the effectiveness of the membrane.ResultsMTZ-NPs membrane had suitable mechanical strength; the drug was released by diffusion. Fourier Transform Infrared Spectroscopy (FTIR), differential scanning calorimetry (DSC), and X-ray diffraction (XRD) results showed the existence of metronidazole might be in the amorphous state in the membrane and had good compatibility with polymers. The in vitro cytotoxicity assays showed that the MTZ-NPs membrane was biocompatible. Cellular uptake of the C6-NPs membrane was significantly higher than that of the C6 membrane (p < 0.0001), signifying that encapsulating the drug in nanoparticles increases drug permeability and improves drug transport efficiency across the cellular membrane. The histological analysis showed that the MTZ-NPs membrane could promote periodontal tissue recovery.ConclusionMTZ-NPs membrane can improve drug penetration delivery into the cells and has a good prospect for the treatment of periodontal disease.
Keywords: drug delivery system